PENGARUH KINERJA LINGKUNGAN DAN BIAYA LINGKUNGAN TERHADAP RETURN ON EQUITY - Piki Muhamad Padilah; Wuri Handayani; Bambang Rustandi; Medianto Suryo (Universitas Sangga Buana, 2025)
The purpose of this study is to determine, analyze, and describe the influence of environmental performance and environmental costs on return on equity. The type of approach in this study is a quantitative approach. This study sample uses a purposive sampling method obtained as many as 15 companies in basic materials companies listed on the Indonesia Stock Exchange for the period 2021-2023 (45 observations). The data used is secondary data. The analytical method used is Panel Data Regression Analysis with the help of the EViews 12 application. The results of the study indicate that partially the environmental performance variable has no effect on return on equity and environmental costs affect return on equity. And simultaneously there is a significant influence between environmental performance and environmental costs on return on equity.